2018
DOI: 10.1177/0958305x18761616
|View full text |Cite
|
Sign up to set email alerts
|

External costs from fossil electricity generation: A review of the applied impact pathway approach

Abstract: This paper reviews and compares eleven studies that have estimated external costs of fossil electricity generation by benefits transfer. These studies include thirteen countries and most of these countries are developing countries. The impact pathway approach is applied to estimate the environmental impact arising from fossil fuel fired power plant's air emission and the related damages on human health. The estimated damages are used to value the monetary external costs from fossil fuel electricity generation.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 44 publications
0
11
0
Order By: Relevance
“…In recent years, the increase in energy consumption is recorded in the industrial [ 1 , 2 ] and global transportation [ 3 , 4 ] sectors, mainly as a result of increased economic activity and mobility of people across the country. Among the various types of energy, fossil energy shows the greatest number of energy consumption to supply global electricity in the industrial and global transportation [ 3 , 5 ]. The massive exploitation of fossil energy leads to the reduction in a large scale of fossil energy, and it takes a long time to be available again in nature, hundreds to thousands of years.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, the increase in energy consumption is recorded in the industrial [ 1 , 2 ] and global transportation [ 3 , 4 ] sectors, mainly as a result of increased economic activity and mobility of people across the country. Among the various types of energy, fossil energy shows the greatest number of energy consumption to supply global electricity in the industrial and global transportation [ 3 , 5 ]. The massive exploitation of fossil energy leads to the reduction in a large scale of fossil energy, and it takes a long time to be available again in nature, hundreds to thousands of years.…”
Section: Introductionmentioning
confidence: 99%
“…Saidi and Omri (2020) also concluded that the best option to reduce CO2 emissions is to consider a mix of nuclear and renewable energy and the two sources of energy are complementary. Meanwhile, the negative externality of the combustion of fossil fuels includes both environmental and public health impacts such as GHG emission, air pollution, and health problems (Jorli et al, 2018). While this study did not account for the other types of externalities, it should be noted that renewables also have negative impacts on the environment.…”
Section: Summary Of Findings and Existing Studiesmentioning
confidence: 96%
“…This approach considers sequential links among the emissions released, their concentrations, their impacts on human beings, and the economic valuation of the resulting damages. Thus, computing the cost of emissions is a multidisciplinary analysis making use of scientific knowledge from several fields [44]. First, the quantity of emissions, for each pollutant, released at specific locations is computed based on the local electricity production per technology, its efficiency and its emission factor.…”
Section: Computation Of the Damage Cost Of Local Pollutantsmentioning
confidence: 99%